Targeting Glutathione-S Transferase Enzymes in Musculoskeletal Sarcomas: A Promising Therapeutic Strategy - Michela Pasello; Maria Cristina Manara; Francesca Michelacci; Marilù Fanelli; Claudia Maria Hattinger; Giordano Nicoletti; Lorena Landuzzi; Pier Luigi Lollini; Annamaria Caccuri; Piero Picci; Katia Scotlandi; Massimo Serra (Analytical Cellular Pathology)
Recent studies have indicated that targeting glutathione-S-transferase (GST) isoenzymes may be a promising novel strategy to improve the efficacy of conventional chemotherapy in the three most common musculoskeletal tumours: osteosarcoma, Ewing's sarcoma, and rhabdomyosarcoma. By using a panel of 15 drug-sensitive and drug-resistant human osteosarcoma, Ewing's sarcoma, and rhabdomyosarcoma cell lines, the efficay of the GST-targeting agent 6-(7-nitro-2,1,3-benzoxadiazol-4-ylthio)hexanol (NBDHEX) has been assessed and related to GST isoenzymes expression (namely GSTP1, GSTA1, GSTM1, and MGST). NBDHEX showed a relevant in vitro activity on all cell lines, including the drug-resistant ones and those with higher GSTs levels. The in vitro activity of NBDHEX was mostly related to cytostatic effects, with a less evident apoptotic induction. NBDHEX positively interacted with doxorubicin, vincristine, cisplatin but showed antagonistic effects with methotrexate. In vivo studies confirmed the cytostatic efficay of NBDHEX and its positive interaction with vincristine in Ewing's sarcoma cells, and also indicated a positive effect against the metastatisation of osteosarcoma cells. The whole body of evidence found in this study indicated that targeting GSTs in osteosarcoma, Ewing's sarcoma and rhabdomyosarcoma may be an interesting new therapeutic option, which can be considered for patients who are scarcely responsive to conventional regimens.